2022
DOI: 10.1108/bfj-10-2021-1077
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of food choice behaviors among college students with food allergies in the US

Abstract: PurposeThis study explored how food allergies have affected food-related behaviors and quality of life of college students with food allergies and identified factors influencing food choice decisions among this group of individuals.Design/methodology/approachOne-on-one interviews were conducted with 26 college students with self-reported or clinically diagnosed food allergies, recruited from two universities located in the southern region of the United States. The participants were asked a series of questions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…The food choices made by university students were influenced by intrapersonal factors such as cooking skills, taste preference, eating habits, level of nutrition-related knowledge, culture, moods, self-efficacy, health and perceptions (Lee et al, 2023). This is because university years often represent the first time when young adults are no longer under the direct supervision of their parents or carers, and they become fully responsible for managing their allergies on their own.…”
Section: Intrapersonal Factors Influence Food Choice Behavior Among U...mentioning
confidence: 99%
See 3 more Smart Citations
“…The food choices made by university students were influenced by intrapersonal factors such as cooking skills, taste preference, eating habits, level of nutrition-related knowledge, culture, moods, self-efficacy, health and perceptions (Lee et al, 2023). This is because university years often represent the first time when young adults are no longer under the direct supervision of their parents or carers, and they become fully responsible for managing their allergies on their own.…”
Section: Intrapersonal Factors Influence Food Choice Behavior Among U...mentioning
confidence: 99%
“…Social environmental factors encompass the individuals and elements that directly influence students within their daily surroundings, including parents, siblings, teachers, and friends at school (Lee et al, 2023). For instance, parental food choices can significantly impact those of their children (Lee et al, 2023).…”
Section: Social Environmental Factors Have An Influence On Food Choic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Food intolerance is due to the body's inability to digest or metabolize a particular food (Bindslev-Jensen, 1998). Food hypersensitivity, regardless of its severity, adversely impacts consumers' dining experiences and further impacts their psychosocial, financial, and emotional well-being, as well as that of their families (Begen et al, 2018;Gupta et al, 2013Gupta et al, , 2018Herbert et al, 2016;Kwon and Lee, 2012;Kwon et al, 2020;Lee et al, 2023;Lieberman et al, 2010;Walkner et al, 2015). Wen and Lee's (2021) survey showed that close to 70% of the participants (N 5 291) in their study had experienced food-based allergic reactions after eating out.…”
Section: Introductionmentioning
confidence: 99%